Turbulence Upstream and Downstream of Interplanetary Shocks - Pitňa, A.; Šafránková, J.; Němeček, Z.; Ďurovcová, T.; Kis, A. (Frontiers in Physics, 2021)
The paper reviews the interaction of collisionless interplanetary (IP) shocks with the turbulent solar wind. The coexistence of shocks and turbulence plays an important role in understanding the acceleration of particles via Fermi acceleration mechanisms, the geoeffectiveness of highly disturbed sheaths following IP shocks and, among others, the nature of the fluctuations themselves. Although our knowledge of physics of upstream and downstream shock regions has been greatly improved in recent years, many aspects of the IP-shock/turbulence interaction are still poorly known, for example, the nature of turbulence, its characteristics on spatial and temporal scales, how it decays, its relation to shock passage and others. We discuss properties of fluctuations ahead (upstream) and behind (downstream) of IP shock fronts with the focus on observations. Some of the key characteristics of the upstream/downstream transition are 1) enhancement of the power in the inertial range fluctuations of the velocity, magnetic field and density is roughly one order of magnitude, 2) downstream fluctuations are always more compressible than the upstream fluctuations, and 3) energy in the inertial range fluctuations is kept constant for a significant time after the passage of the shock. In this paper, we emphasize that–for one point measurements–the downstream region should be viewed as an evolutionary record of the IP shock propagation through the plasma. Simultaneous measurements of the recently launched spacecraft probing inner parts of the Solar System will hopefully shed light on some of these questions.